Anti‐inflammatory properties of ophioglonin derived from the fern Ophioglossum vulgatum L. via inactivating NF‐κB and MAPK signaling pathways - Xiaoqing Zhu; Cheng Tian; Dan Yao; Siqi Li; Junjiang Lv; Yongwen Chen; Xiaoyong Huang (FEBS Open Bio)
Medicinal plants contain bioactive compounds that have therapeutic effects on human health. Ophioglossum vulgatum L. is a representative species of the fern genus Ophioglossum that has anti‐inflammatory properties as recognized in folk medicine. Herein, we performed a nitric oxide (NO) assay‐guided screening in RAW264.7 cells to investigate the active components of the plant. We found that ophioglonin (OPN), a characteristic homoflavonoid of the genus Ophioglossum, is one of the bioactive components. Therefore, we performed a comparative analysis of the isolated compounds and found that OPN has effects similar to those of isolated dihydroquercetin and luteolin at the concentrations tested. The antioxidant and anti‐inflammatory activities of OPN were extensively validated using lipopolysaccharide ‐stimulated RAW264.7 cells, mouse bone marrow‐derived macrophages (BMDMs), and peritoneal exudate macrophages (PEMs). In vivo experiments with a carrageenan‐induced mouse paw edema model further confirmed the anti‐inflammatory effect of OPN. Additionally, we found that OPN and Ophioglossum vulgatum extracts inhibit the activation of signal transducers, NF‐ĸB p65, IĸBα, ERK, p38, and JNK, consistent with the findings of pathway enrichment analysis. This work reinforces the anti‐inflammatory properties of Ophioglossum vulgatum and indicates that OPN is a promising therapeutic agent for inflammation‐associated disorders. Further clinical evaluations, including clinical trials, would be beneficial to validate the anti‐inflammatory properties of OPN.